The Effects of Banning Advertising in Junk Food Markets. (6th April 2017) - Dubois, Pierre; Griffith, Rachel; O'Connell, Martin
Abstract: There are growing calls to restrict advertising of junk foods. Whether such a move will improve diet quality will depend on how advertising shifts consumer demands and how firms respond. We study an important and typical junk food market—the potato chips market. We exploit consumer level exposure to adverts to estimate demand, allowing advertising to potentially shift the weight consumers place on product healthiness, tilt demand curves, have dynamic effects and spillover effects across brands. We simulate the impact of a ban and show that the potential health benefits are partially offset by firms lowering prices and by consumer switching to other junk foods.